RESORT DENGAN PENDEKATAN EKOLOGI ARSITEKTUR DI PANTAI NAMPU WONOGIRI - Triska Adi Kusumadewi; Widi Suroto; Agus Heru Purnomo (Universitas Sebelas Maret Surakarta, 2016)
Wonogiri contains great potential in the tourism sector. The local government have current programs to develops 9 DPK (Destinasi Pariwisata Kabupaten), one is Nampu Beach. Nampu Beach has natural scenery in the form of a charming white sand, and the waves that collided with a rock. These waves are very heavy because Nampu Beach is included in the row of the south coast which is directly related to the Indian Ocean. Until now, Nampu Beach still remains the responsibility of citizens around the coast to reap revenue. There is no qualified places for Nampu’s tourists yet. Nampu Beach requires a resort to accommodate visitor activities. Resort refers to building or a group of buildings designed in a particular setting to cater for both relax and recreational activities. This resort plan design and development concerning environmental issues that carry out the ecological concept. There will be a balance between human and nature in this resort design and plan. Ecological Architecture can be applied to the design of resort in the regulation of site, shape, building mass, and composition of site. The existence of resort in Nampu Beach is expected will be Wonogiri new icon. Keywords: Ecological Design, Pantai Nampu Wonogiri, Resort